Quantitative evaluation of aerosol generation during manual facemask ventilation. (26th October 2021) - Shrimpton, A. J.; Brown, J. M.; Gregson, F. K. A.; Cook, T. M.; Scott, D. A.; McGain, F.; Humphries, R. S.; Dhillon, R. S.; Reid, J. P.; Hamilton, F.; Bzdek, B. R.; Pickering, A. E.; et al.
Summary: Manual facemask ventilation, a core component of elective and emergency airway management, is classified as an aerosol‐generating procedure. This designation is based on one epidemiological study suggesting an association between facemask ventilation and transmission during the SARS‐CoV‐1 outbreak in 2003. There is no direct evidence to indicate whether facemask ventilation is a high‐risk procedure for aerosol generation. We conducted aerosol monitoring during routine facemask ventilation and facemask ventilation with an intentionally generated leak in anaesthetised patients. Recordings were made in ultraclean operating theatres and compared against the aerosol generated by tidal breathing and cough manoeuvres. Respiratory aerosol from tidal breathing in 11 patients was reliably detected above the very low background particle concentrations with median [IQR (range)] particle counts of 191 (77–486 [4–1313]) and 2 (1–5 [0–13]) particles.l ‐1, respectively, p = 0.002. The median (IQR [range]) aerosol concentration detected during facemask ventilation without a leak (3 (0–9 [0–43]) particles.l ‐1 ) and with an intentional leak (11 (7–26 [1–62]) particles.l ‐1 ) was 64‐fold (p = 0.001) and 17‐fold (p = 0.002) lower than that of tidal breathing, respectively. Median (IQR [range]) peak particle concentration during facemask ventilation both without a leak (60 (0–60 [0–120]) particles.l ‐1 ) and with a leak (120 (60–180 [60–480]) particles.l ‐1 ) were 20‐fold (p = 0.002) and 10‐fold (0.001) lower than a cough (1260 (800–3242 [100–3682]) particles.l ‐1 ), respectively. This study demonstrates that facemask ventilation, even when performed with an intentional leak, does not generate high levels of bioaerosol. On the basis of this evidence, we argue facemask ventilation should not be considered an aerosol‐generating procedure.